PENGARUH METODE PROYEK DALAM MENSTIMULASI KETERAMPILAN KOLABORASI ANAK USIA DINI: PERSEPSI GURU ANAK USIA DINI DI KOTA PADANG - Oktaviani, Prity; Afnida, Mutia; Anggraini, Vivi; Syafnita, Tisna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The significance of fostering early childhood collaboration skills as a component of social development necessitating the implementation of suitable instructional strategies in kindergarten is the driving force behind this research. This study seeks to gather insights from kindergarten teachers in Padang City regarding the impact of the project method on early childhood collaboration skills. This study used a quantitative survey approach. Participants were 102 kindergarten teachers across 11 sub-districts in Padang City. Simple random sampling was used for sampling, and simple regression analysis was used. The findings demonstrated that the project approach significantly impacted the development of early children's capacity for teamwork. Children learn to collaborate in groups, divide up responsibilities, communicate, and handle disagreements amicably through the use of the project approach. It follows that kindergarteners can benefit greatly from learning to work together through the project technique.